Economic Decisions under Inflation: The Impact of Accounting Measurement Errors (Book). - Belkaoui, Ahmed; Meyer, Philip E. (The Accounting Review, 1983)
Reviews the book "Economic Decisions Under Inflation: The Impact of Accounting Measurement Errors," by Stephen M. Cross.